Parent-Child Communication Incongruence in Pediatric Healthcare - Nancy Kwun Yiu Ng; Joanne Dudeney; Tiina Jaaniste (MDPI AG, 2023)
Parents play a key role in providing children with health-related information and emotional support. This communication occurs both in their homes and in pediatric healthcare environments, such as hospitals, outpatient clinics, and primary care offices. Often, this occurs within situations entailing heightened stress for both the parent and the child. There is considerable research within the communication literature regarding the nature of both verbal and nonverbal communication, along with the way in which these communication modalities are either similar (i.e., congruent) or dissimilar (i.e., incongruent) to one another. However, less is known about communication congruency/incongruency, specifically in parent-child relationships, or within healthcare environments. In this narrative review, we explore the concept of verbal and nonverbal communication incongruence, specifically within the context of parent-child communication in a pediatric healthcare setting. We present an overview of verbal and nonverbal communication and propose the Communication Incongruence Model to encapsulate how verbal and nonverbal communication streams are used and synthesized by parents and children. We discuss the nature and possible reasons for parental communication incongruence within pediatric settings, along with the consequences of incongruent communication. Finally, we suggest a number of hypotheses derived from the model that can be tested empirically and used to guide future research directions and influence potential clinical applications.